GAMBARAN FAKTOR-FAKTOR PENYEBAB SESEORANG MENJADI HOMOSEKSUAL PADA LAKI-LAKI - muhammad rivai (Jurnal Ilmu Keperawatan, 2018)
HANGTUAH PEKANBARU HEALTH SCHOOL BACHELOR DEGREE of NURSING PROGRAME Research, February 2018 Muhammad Rivai Factors Causing Someone to Be Homosexual In Men xi + 50 pages + 7 tables + 2 schemes + 5 attachments ABSTRACT Sexual orientation is an emotional and sexual attraction to a particular gender. Normally sexual orientation is done with the opposite sex. Homosexual is a sexual deviation that can be formed by various factors namely psychological factors, new psychoanalytic factors, and biological factors. Therefore, researchers interested in doing research on the description of factors causing a person to be homosexual. This study aims to identify the description of factors causing a person to be homosexual. This research uses quantitative research type with descriptive design. The population in this study is all people who have criteria as homosexual and the number of samples taken as many as 89 people in accordance with the inclusion criteria by purposive sampling method. The results of this study are known from 89 respondents menyatkan psychological factors that cause the respondents to homosexual men is I feel less get noticed by my parents I never do same-sex sexual activity for the money given 51 respondents (57.30%) New psychoanalytic factors I am very idolized and very love my father as much as51 responden (57,30%) biological factor is I feel have character like woman (feminim counted 51 respondent (57,30%) hopefully with this research can be reading material in dig and find out more about the factors causing a person to be homosexual References: 40 References (2004. -2017) Keywords: Cause, Homosexual, Men